2016
DOI: 10.1155/2016/5189741
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy Coexisting with Acute Pericarditis and Myocardial Bridge

Abstract: Takotsubo cardiomyopathy (TCM) is a stress-induced cardiomyopathy that occurs primarily in postmenopausal women. It mimics clinical picture of acute coronary syndrome with nonobstructive coronary arteries and a characteristic transient left (or bi-) ventricular apical ballooning at angiography. The exact pathogenesis of TCM is not well recognized. Hereby we present an unusual case of TCM that presents with signs and symptoms of acute pericarditis and was also found to have a coexisting coronary muscle bridge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…To explain the confounding clinical picture, we support the “inflammatory hypothesis”. According to this proposed mechanism, SIC can be considered a variant of regional inflammatory myocarditis with extension of the myocardial inflammation to the overlying pericardium, leading to pericarditis [2729]. The evidence of inflammation of the myocardium has been previously reported both on endomyocardial biopsy [27,30] and on cMRI [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explain the confounding clinical picture, we support the “inflammatory hypothesis”. According to this proposed mechanism, SIC can be considered a variant of regional inflammatory myocarditis with extension of the myocardial inflammation to the overlying pericardium, leading to pericarditis [2729]. The evidence of inflammation of the myocardium has been previously reported both on endomyocardial biopsy [27,30] and on cMRI [31].…”
Section: Discussionmentioning
confidence: 99%
“…According to this proposed mechanism, SIC can be considered a variant of regional inflammatory myocarditis with extension of the myocardial inflammation to the overlying pericardium, leading to pericarditis [2729]. The evidence of inflammation of the myocardium has been previously reported both on endomyocardial biopsy [27,30] and on cMRI [31]. The role of intense catecholamine surge secondary to the chest pain caused by pericardial inflammation has also been proposed and may explain how pericarditis can trigger SIC [27,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported a case in which an 84‐year‐old woman was diagnosed as having TTS with acute pericarditis as revealed on ECG. Currently, numerous studies demonstrate the coexistence of acute pericarditis and TTS . In these studies, several cases of PR deviation can be found.…”
Section: Discussionmentioning
confidence: 99%
“…To explain the confounding clinical picture, we support the "inflammatory hypothesis". According to this proposed mechanism, SIC can be considered a variant of regional inflammatory myocarditis with extension of the myocardial inflammation to the overlying pericardium, leading to pericarditis [27][28][29]. The evidence of inflammation of the myocardium has been previously reported both on endomyocardial biopsy [27,30] and on cMRI [31].…”
mentioning
confidence: 99%